O lazer , os jovens e a escola: territórios, acontecimentos e conhecimentos no cotidiano de uma escola pública, de ensino fundamental, no município de Belo Horizonte - Mariana Soares Ferraz Malta (2015)
Think the relationship leisure, youth and school was the challenge of this work, seeking to perceive and understand the relationships that happen between the boys and girls, every day, beyond the walls of the classrooms. A living, latent school, which is invented and turns every day. Experiences, cultural practices, games that makes the time and the space between school entry and exit are lived in various ways. For that, I needed to understand the complexity and multiplicity of relationships within the school. I sought knowledge of research methods that could give me the necessary support for research to which I set out. I found in ethnography and cartography some possible paths for this route. The dialogue of methodological actions of these two procedures has helped me to better understand the object of study. I decided to "look closely and from the inside" (Magnani, 2012), using participant observation as it needed to be in this school, observe the movement of students, make records images, records in my diary, talk to them to try to capture the most of the young universe within the school context, these tools used in the ethnographic process. But ultimately, what students do in school life? As they are in the school context? How do they appropriate the times and spaces? What are the meanings given by them to the experience in school? What knowledge they produce beyond those that the school waiting for an answer? What are the experiments, exchange of experiences, teaching and learning that can be perceived in these moments? I sought to identify, in everyday school life this wealth of expressions of the students, the relations between them, the space and time and its reinterpretation. I watched various events, social practices that showed me how rich experiences there at times when students are not in the room. Games, jokes, conversations with friends, moments of prayer are some of the many experiences for them in the playground. I saw the school as a multicultural space, where leisure is experienced in different ways, this interrelations